Highly selective synthesis of (E)-alkenyl-(pentafluorosulfanyl)benzenes through Horner–Wadsworth–Emmons reaction - Iakobson, George; Beier, Petr (Beilstein Journal of Organic Chemistry, 2012)
Diethyl 2-nitro-(pentafluorosulfanyl)benzylphosphonates, available by the vicarious nucleophilic substitution reaction of meta- and para-nitro-(pentafluorosulfanyl)benzenes and diethyl chloromethylphosphonate, undergo Horner–Wadsworth–Emmons reaction with aldehydes in the presence of potassium hydroxide in acetonitrile at ambient temperature to give (E)-2-nitro-1-alkenyl-(pentafluorosulfanyl)benzenes in good yields and high stereoselectivities. Follow-up transformations of the primary products provided (E)-1-alkenyl-(pentafluorosulfanyl)benzenes and 2-(2-arylethyl)-(pentafluorosulfanyl)anilines.
Keywords: Horner–Wadsworth–Emmons reaction; pentafluorosulfanyl group; phosphonates; sulfurpentafluoride

(untitled) - Case, J. R.; Ray, N. H.; Roberts, H. L. (J. Chem. Soc., 1961)

(untitled) - Ray, N. H. (J. Chem. Soc., 1963)

(untitled) - Merrill, C. I.; Cady, G. H. (J. Am. Chem. Soc., 1961)

(untitled) - Dudley, F. B.; Cady, G. H.; Eggers, D. F., Jr (J. Am. Chem. Soc., 1956)

Modern Fluoroorganic Chemistry - Kirsch, P. (Synthesis of complex Organofluorine Compounds, 2004)

Fluorine-Containing Synthons - Winter, R. W.; Dodean, R. A.; Gard, G. L. (SF5-Synthons: Pathways to Organic Derivatives of SF6, 2005)

Current Fluoroorganic Chemistry - Kirsch, P.; Röschenthaler, G.-V. (Functional Compounds Based on Hypervalent Sulfur Fluorides, 2007)

(untitled) - Aït-Mohand, S.; Dolbier, W. R., Jr (Org. Lett., 2002)

(untitled) - Dolbier, W. R., Jr; Aït-Mohand, S.; Schertz, T. D.; Sergeeva, T. A.; Cradlebaugh, J. A.; Mitani, A.; Gard, G. L.; Winter, R. W.; Thrasher, J. S. (J. Fluorine Chem., 2006)

WO Patent - Bowden, R. D.; Greenhall, M. P.; Moilliet, J. S.; Thomson, J. (The Preparation Of Fluorinated Organic Compounds, 1997)

(untitled) - Bowden, R. D.; Comina, P. J.; Greenhall, M. P.; Kariuki, B. M.; Loveday, A.; Philp, D. (Tetrahedron, 2000)

(untitled) - Chambers, R. D.; Spink, R. C. H. (Chem. Commun., 1999)

(untitled) - Umemoto, T.; Garrick, L. M.; Saito, N. (Beilstein J. Org. Chem., 2012)

U.S. Patent Appl. - Umemoto, T.; Chika, J. (Processes for preparing 1,3-dinitro-5-(pentafluorosulfanyl)benzene and its intermediates, 2011)

(untitled) - Beier, P.; Pastýříková, T.; Vida, N.; Iakobson, G. (Org. Lett., 2011)

(untitled) - Beier, P.; Pastýříková, T.; Iakobson, G. (J. Org. Chem., 2011)

(untitled) - Beier, P.; Pastýříková, T. (Tetrahedron Lett., 2011)

(untitled) - Pastýříková, T.; Iakobson, G.; Vida, N.; Pohl, R.; Beier, P. (Eur. J. Org. Chem., 2012)

(untitled) - Vida, N.; Beier, P. (J. Fluorine Chem.)

(untitled) - Crowley, P. J.; Mitchell, G.; Salmon, R.; Worthington, P. A. (Chimia, 2004)

(untitled) - Kirsch, P.; Bremer, M.; Heckmeier, M.; Tarumi, K. (Angew. Chem., Int. Ed., 1999)

(untitled) - Sheppard, W. A. (J. Am. Chem. Soc., 1962)

(untitled) - Maryanoff, B. E.; Reitz, A. B. (Chem. Rev., 1989)

(untitled) - Boutagy, J.; Thomas, R. (Chem. Rev., 1974)

(untitled) - Rein, T.; Pedersen, T. M. (Synthesis, 2002)

(untitled) - Ando, K. (J. Synth. Org. Chem., Jpn., 2000)

(untitled) - Ando, K. (J. Org. Chem., 1997)

(untitled) - Still, W. C.; Gennari, C. (Tetrahedron Lett., 1983)